REPRESENTASI MUSLIMAH DI INSTAGRAM (ANALISIS SEMIOTIKA ROLAND BARTHES PADA AKUN @HIJABOGRAPHIC) - Deli Luthfi Rahman (Berajah Journal, 2026)
The revolution in communication and information technology has ushered in a new era in media, also known as ‘new media’, where its presence is inextricably linked to computer-mediated and internet-based communication devices. One such new media technology is the emergence of the social media platform Instagram. Recently, Instagram has expanded its features to make the platform more comprehensive and enjoyable for its users. This trend has transformed social media into a new space for interaction and communication, attracting individuals and even communities to engage within it. One such community on Instagram is the Hijabografi community. This is a community that utilises graphic design as a medium to convey its message. In their Instagram posts, the Hijabografi community consistently features images of Muslim women wearing the hijab. The Hijabografi community has a specific aim in presenting this imagery. Ideas and concepts regarding Muslim women can be found in their Instagram posts. Indirectly, the Hijabografi account constructs an image of Muslim women in the digital space, where values concerning Muslim women are displayed. This study aims to uncover the signs within the posted images and to understand how Muslim women are represented on the Hijabografi Instagram account. The use of language in the form of images, words, sequences, narratives and so on, in Hijabografi’s Instagram posts, represents its perspective on Muslim women. To uncover the representation of Muslim women, Roland Barthes’s semiotics was employed; in his theory, Barthes examines meaning or symbols in language or signs, which are divided into two levels of significance—the denotative and connotative levels—as well as other aspects of signification, namely myth. From the seventeen hijab-wearing Instagram posts analysed, it was revealed that Muslim women possess piety, equality, freedom, strength, intelligence and independence, and these posts demonstrate three representations of Muslim women: firstly, the hijab as a symbol of Muslim women’s religious faith; secondly, the equality of Muslim women and Muslim men; and thirdly, the relationship between the roles of Muslim women and men. Overall, the conclusion regarding the representation of Muslim women on hijab-wearing Instagram accounts is that Muslim women are pious, noble, intelligent and active.